A New Angle-Based Location Method Using a Forward-Link Signal. (10th August 2009) - Song, Seung-Hun; Im, Hyun-Ja; Park, Ji-Won; Sung, Tae-Kyung
Abstract : With conventional AOA positioning using a reverse-link signal, each sensor is equipped with an array antenna to measure the incident angle of the signal emitting by a mobile source. In order to perform the complicated array processing for angle measurements, both the sensor size and the power consumed by the sensor can increase in RLAOA (reverse-link AOA) positioning. In some applications such as mobile vehicle localization, the vehicle has fewer limitations in terms of size or power consumption. Rather, it is desirable to make the sensor as light as possible. This paper presents a new angle-based positioning scheme using a forward-link signal. Under the assumption that a ground vehicle moves on a horizontal surface, a measurement equation for the FLAOA (forward-link AOA) is initially derived. Using the measurement equation, a closed-form solution for FLAOA positioning is proposed. With the proposed method, it is also possible to estimate the azimuth of the vehicle as well as its position. The performance of the proposed method is compared to that of RLAOA positioning in a computer simulation. The simulation results show that the proposed method is potentially suitable for applications involving the localization and guidance of mobile vehicles.